2018
DOI: 10.1186/s40478-018-0644-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transfer from mesenchymal stem cells to neural stem cells protects against the neurotoxic effects of cisplatin

Abstract: Mesenchymal stem cells (MSCs) transfer healthy mitochondria to damaged acceptor cells via actin-based intercellular structures. In this study, we tested the hypothesis that MSCs transfer mitochondria to neural stem cells (NSCs) to protect NSCs against the neurotoxic effects of cisplatin treatment. Our results show that MSCs donate mitochondria to NSCs damaged in vitro by cisplatin. Transfer of healthy MSC-derived mitochondria decreases cisplatin-induced NSC death. Moreover, mitochondrial transfer from MSCs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 48 publications
3
104
0
1
Order By: Relevance
“…Accumulating evidence has shown that mitochondrial transfer occurs via TNTs, gap junctions, microvesicles, cell fusion and transfer of isolated mitochondria [132,[242][243][244][245]. So far, mitochondrial transfer from MSCs has demonstrated protective effects in lung injury, bronchial epithelial injury, allergic diseases, damaged cardiomyocytes, alkali-burnt corneal epithelial cells, kidney injury, ischemic damage, neurotoxicity, and spinal cord injury [132,[246][247][248][249][250][251][252][253]. Numerous studies have identified several signals including release of damaged mitochondria, mtDNA and mitochondrial products along with elevated ROS levels that trigger mitochondrial transfer from MSCs to the recipient cells [241].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…Accumulating evidence has shown that mitochondrial transfer occurs via TNTs, gap junctions, microvesicles, cell fusion and transfer of isolated mitochondria [132,[242][243][244][245]. So far, mitochondrial transfer from MSCs has demonstrated protective effects in lung injury, bronchial epithelial injury, allergic diseases, damaged cardiomyocytes, alkali-burnt corneal epithelial cells, kidney injury, ischemic damage, neurotoxicity, and spinal cord injury [132,[246][247][248][249][250][251][252][253]. Numerous studies have identified several signals including release of damaged mitochondria, mtDNA and mitochondrial products along with elevated ROS levels that trigger mitochondrial transfer from MSCs to the recipient cells [241].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…Oxygen consumption rates were normalized to the total protein content of each well. Basal respiration, maximal respiratory capacity, and spare respiratory capacity were determined as described previously (Boukelmoune et al, 2018).…”
Section: Analysis Of Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…Mitochondrial transfer from one cell type to another is not exclusive to astrocytes and neurons. For example, we and others have shown that mesenchymal stem cells transfer mitochondria to damaged neuronal stem cells thereby improving stem cell survival and mitochondrial membrane potential in the recipient cells (Boukelmoune et al, 2018;Gheusi and Lledo, 2014; M. L. Babenko et al, 2018). Transfer of mitochondria from one cell to another occurs via multiple mechanisms such as release and uptake of vesicles, transfer via gap junctions, and transfer via F-actin based tunneling nanotubes (Rogers and Bhattacharya, 2013;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial transfer from one cell type to another is not exclusive to astrocytes and neurons [19]. For example, we and others have shown that mesenchymal stem cells transfer mitochondria to damaged neuronal stem cells thereby improving stem cell survival and mitochondrial membrane potential in the recipient cells [20][21][22]. Transfer of mitochondria from one cell to another occurs via multiple mechanisms such as release and uptake of vesicles, transfer via gap junctions, and transfer via F-actin based tunneling nanotubes [17,23].…”
Section: Introductionmentioning
confidence: 99%